Spatial patterns of large African cats: a large‐scale study on density, home range size, and home range overlap of lions Panthera leo and leopards Panthera pardus. (6th March 2023) - Nams, Vilis O.; Parker, Dan M.; Weise, Florian J.; Patterson, Bruce D.; Buij, Ralph; Radloff, Frans G. T.; Vanak, Abi Tamim; Tumenta, Pricelia N.; Hayward, Matt W.; Swanepoel, Lourens H.; Funston, Paul J.; Bauer, Hans; et al.
Abstract: Spatial patterns of and competition for resources by territorial carnivores are typically explained by two hypotheses: 1) the territorial defence hypothesis and 2) the searching efficiency hypothesis. According to the territorial defence hypothesis, when food resources are abundant, carnivore densities will be high and home ranges small. In addition, carnivores can maximise their necessary energy intake with minimal territorial defence. At medium resource levels, larger ranges will be needed, and it will become more economically beneficial to defend resources against a lower density of competitors. At low resource levels, carnivore densities will be low and home ranges large, but resources will be too scarce to make it beneficial to defend such large territories. Thus, home range overlap will be minimal at intermediate carnivore densities. According to the searching efficiency hypothesis, there is a cost to knowing a home range. Larger areas are harder to learn and easier to forget, so carnivores constantly need to keep their cognitive map updated by regularly revisiting parts of their home ranges. Consequently, when resources are scarce, carnivores require larger home ranges to acquire sufficient food. These larger home ranges lead to more overlap among individuals' ranges, so that overlap in home ranges is largest when food availability is the lowest. Since conspecific density is low when food availability is low, this hypothesis predicts that overlap is largest when densities are the lowest. We measured home range overlap and used a novel method to compare intraspecific home range overlaps for lions Panthera leo ( n  = 149) and leopards Panthera pardus ( n  = 111) in Africa. We estimated home range sizes from telemetry location data and gathered carnivore density data from the literature. Our results did not support the territorial defence hypothesis for either species. Lion prides increased their home range overlap at conspecific lower densities whereas leopards did not. Lion pride changes in overlap were primarily due to increases in group size at lower densities. By contrast, the unique dispersal strategies of leopards led to reduced overlap at lower densities. However, when human‐caused mortality was higher, leopards increased their home range overlap. Although lions and leopards are territorial, their territorial behaviour was less important than the acquisition of food in determining their space use. Such information is crucial for the future conservation of these two iconic African carnivores. Abstract : Animals need to move to find food, search for mates, and interact with other species. When the amount of food decreases, then animals change their movements. Two of the factors that could determine how they change are: 1) the need to defend their food and 2) searching efficiency. If the most important factor is 1) defence, then we would expect the lowest home range overlap to occur among individuals at intermediate resource availability. If the most important factor is 2) searching efficiency, then we would expect the lowest overlap to occur among individuals at high resource availability. We tested hypotheses based on these expectations using movement datasets of lions and leopards. The pattern in lions suggests that searching efficiency is the most important factor, with the key behavioural change being that they form larger groups at low resource availability. Large groups are more efficient at finding prey. Leopards show neither pattern and have similar home range overlap at all values of food abundance. The pattern in leopards is likely to be due to efficient searching and killing by humans.